Analysis of Risk Factors for the Incidence of Coronary Heart Disease - Audatur Rahmiyah; Irfansyah Baharuddin Pakki; Iwan Muhamad Ramdan (Indonesian Journal of Global Health Research, 2025)
Coronary Heart Disease (CHD) is a significant public health problem with high morbidity and mortality. Although CHD cases continue to increase in Indonesia, including in East Kalimantan, there have not been many studies that have identified specific risk factors at Kudungga Sangatta Hospital, East Kutai Regency. This study aims to analyze the risk factors for CHD incidence at Kudungga Sangatta Hospital. This study uses an analytical observational design with a case-control approach. The sample consisted of 60 cases of CHD and 60 non-CHD controls taken from outpatients at the cardiac polyclinic of Kudungga Sangatta Hospital using purposive sampling techniques. Data was collected through questionnaires and medical records. Independent variables include hypertension, family history, and hypercholesterolemia, while dependent variables are CHD incidence. The data collection techniques included a preparation stage (obtaining research permits and conducting a preliminary study), followed by an implementation stage (collecting respondent data, sorting samples according to criteria into two groups, filling out questionnaires, and collecting research instruments). Data analysis was done quantitatively using a case control design with the chi-square test to see the relationship between variables. This study found a significant association with the incidence of dengue in the following variables: hypertension (p < 0.000) OR 10,394, family history (p < 0.000) OR 7.538, and hypercholesterolemia (p < 0.000) OR 10.846. It can be concluded that hypertension is the most dominant risk factor affecting the incidence of coronary heart disease at Kudungga Sangatta Hospital (Exp (β) = 11,311).